Pengaruh Minat Penggunaan E-Filing dalam Pelaporan SPT Orang Pribadi dengan Pemahaman Internet sebagai Variabel Moderasi Berbasis pendekatan Technology Acceptance Model (TAM) - Liza Suryadi; Adnan, Ifanny Adnan Pratama (LPPM STIE PPI, 2025)
Introduction/Objective: This study aims to examine the influence of accounting knowledge and experience on business development with the use of accounting information as an intervening variable. Background of the Problem: MSMEs need business development driven by aspects of accounting information and knowledge and business experience by producing various varied results. Novelty: Analyzing the same variables according to previous research but adding intervening variables on MSME actors. Research Method: Using a quantitative approach, data was taken from MSME actors and samples using a random method with criteria obtained 37 samples and the analysis used was path analysis. Findings/Results: Accounting knowledge influences the use of accounting information and business development, business experience influences capital structure, use of accounting information and business development. The use of accounting information has a negative effect on business development and accounting knowledge and business experience do not mediate business development through the use of accounting information. Conclusion: These findings provide important implications in paying attention to global and technical economic factors so that they can be used as considerations before developing and investing in a company.